Pengelolaan Penggunaan LCD Proyektor sebagai Sarana Cognitive Ergonomic dalam Proses Pembelajaran - Boby Yasman Purnama; Farwati, Sizka; Putri, Nadella (Jurnal Pendidikan Madrasah, 2025)
LCD (Liquid Crystal Display) projectors play a crucial role in integrating educational technology, yet their utilization remains suboptimal due to limited user proficiency. This study aims to describe the management and policy of LCD projector use as a cognitive ergonomic tool at SMP Islam Al-Azhar 57 Jambi. A descriptive qualitative approach was employed through observation, documentation, and in-depth interviews, analyzed using source triangulation. Findings reveal: (1) Projector management is systematically implemented through procurement, centralized borrowing, and basic maintenance, although formal SOPs and technical training are lacking. (2) The use of LCD projectors significantly enhances visual comfort, attention focus, productivity, and reduces eye strain, creating a more effective and conducive learning environment. (3) Flexible school policies supported by borrowing and monitoring systems optimize utilization, despite the absence of formal documentation. The study implies that LCD projectors serve not only as instructional media but also as tools contributing to cognitive comfort and improved educational quality.